Divinity and Experience : The Religion of the Dinka - Lienhardt, Godfrey (Oxford University Press, 1961)
According to the Dinka people of the Southern Sudan, man and his creator were originally close together. They became separated, like the earth and sky, when the first man and woman acted with human independence. Dinka religious practice follows from that separation. Divinity and Experience, now reissued for the first time in paperback, has, since its first publication in 1961, acquired the status of a minor classic of social anthropology. In the first section, the various divinities of the Dinka are described with their complex range of meaning and imagery, andrelated to the Dinka's own experience of the conditions of life and death. They may be interpreted, it is suggested, as images arising out of that experience. The second part discusses the role of the priests, the "masters of the fishing spear", who interested Fraser in his study of divine worship. Sacrifices are described and their meaning analysed, and finally their rites at the death of priests, some of whom may enter the grave alive, are examined. Translations of hymns, prayers, and myths are also provided, which serve as a good introduction to the thought and beliefs of the Dinka for those interested in religion and its interpretation.